Electrical and optical properties of ZnO-milled Fe2O3 nanocomposites produced by powder metallurgy route - Guler, Seval Hale; Guler, Omer; Evin, Ertan; Islak, Serkan (Elsevier Gmbh, 2016)
In this study, ZnO-Fe2O3 nanocomposites were synthesized by powder metallurgy route and characterized through X-ray diffraction, UV-vis diffuse reflectance spectroscopy, scanning electron microscopy, electrical conductivity measurement device. The amount of Fe2O3 in the ZnO and milling time were varied in order to investigate their influence on the electrical and optical properties of the samples. Powder mixture containing milled and unmilled Fe2O3 at the rates of the 1, 3 and 5 wt% was sintered in vacuum environment. Results show that the conductivities of ZnO Fe2O3 nanocomposites slightly increased by increasing the Fe2O3 content and these composites have potential materials for photocatalysis. Besides, electrical and optical properties of ZnO Fe2O3 nanocomposites varied according to status of unmilled Fe2O3 and milled Fe2O3. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: ZnO-Fe2O3 nanocomposites; Electrical properties; Optical properties; Milling